σ(28)-Dependent Transcription in Salmonella enterica Is Independent of Flagellar Shearing - Rosu, Valentina (American Society for Microbiology, 2006)
The FlgM anti-σ(28) factor is secreted in response to flagellar hook-basal body completion to allow σ(28)-dependent transcription of genes needed late in flagellar assembly, such as the flagellin structural gene, fliC. A long-standing hypothesis was that one role of FlgM secretion was to allow rapid expression of flagellin in response to shearing. We tested this hypothesis by following FlgM secretion and fliC transcription in response to flagellar shearing. Experiments showed that the level of FlgM inside the cell was unchanged after shearing whereas the extracellular FlgM levels increased in the growth medium as time passed. Identical results were obtained with cells that were not exposed to shear forces: internal FlgM levels remained constant while external FlgM levels rose with time at rates similar to those for the sheared culture. Consistent with this find, FlgM/σ(28)-dependent class 3 gene expression was unaffected by flagellar shearing but was affected by the growth phase of the cell. Regardless of exposure to shear forces, flagellar class 3 transcription rose sharply and then declined. These results demonstrate that flagellar regrowth following shearing is independent of FlgM secretion.